Rupture Process of the Mw 3.3 Earthquake in the St. Gallen 2013 Geothermal Reservoir, Switzerland. Issue 14 (22nd July 2019) - Király‐Proag, E.; Satriano, C.; Bernard, P.; Wiemer, S.
Abstract: We analyze slip distribution and rupture kinematics of a M w 3.3 induced event that occurred in the St. Gallen geothermal reservoir (NE Switzerland) in 2013. We carry out a two‐step procedure: (1) path effects are deconvolved from the seismograms using an empirical Green's function, resulting in relative source time functions at all seismic stations; (2) the relative source time functions are back‐projected to the corresponding isochrones on the fault plane. Results reveal that the mainshock rupture propagates toward NNE from the hypocenter with an average velocity of 2, 000 m/s. Spatiotemporal organization of foreshocks and aftershocks shows that the mainshock broke a previously less active portion of the fault and suggests that the aftershock sequence could be mainly driven by stress transfer. Applying this method in an operational environment could enable fast retrieval of seismic slip, allowing assessment of fault asperities and structures involved in the reservoir creation process. Plain Language Summary: In most models and analyses, small earthquakes (i.e., magnitude less than 4) are considered either point sources or homogeneous "penny‐shaped" surfaces. While these assumptions may be valid, details of earthquake ruptures are more complex. Here we study a magnitude 3 induced earthquake that occurred in the St. Gallen geothermal reservoir (NE Switzerland) in 2013. We image the earthquake rupture by refocusing on the fault the seismic energy recorded at six sensors located within 15 km from the source. Our results show that a detailed description of the rupture process of such a small earthquake can indeed be obtained: The rupture propagates from the hypocenter in NNE direction for 150 m, with an average velocity of 2 km/s, breaking into a less active portion of the fault, where no earthquake was previously recorded. The proposed method could be routinely applied during geothermal reservoir operations to allow rapid assessment of fault structures involved in the reservoir creation process. Key Points: Our approach reveals rupture complexity for a magnitude 3.3 fluid‐induced earthquake at 100‐m scale The rupture propagated toward NNE, breaking into a previously less active portion of the fault Early aftershocks distribute around the main slip area, suggesting a stress transfer mechanism